The Happiness of Smallholder Layer-Chicken Farmers in Rural of East Java, Indonesia - Sutawi Sutawi; D. Karmiyati; D. Iswatiningsih (Faculty of Animal Science, Bogor Agricultural University, 2020)
This study was conducted to measure the level of happiness of smallholder layer-chicken farmers in rural East Java based on the subjective well-being conditions. The study was conducted in April 2019 with a survey method in the Malang Regency of East Java Province. Analysis units were 109 (20%) smallholder layer chicken households purposively selected from 543 poultry farmers. Data collection was carried out through interviews using structured questionnaires and assistive tools of scoring on questions related to the dimensions of life satisfaction, affect, and eudaimonia that represent the ladder of life scale on a scale of 0 to 10. The three dimensions were divided into 19 indicators and used to calculate the Happiness Index. Smallholder layer chicken farmers said that they were “Satisfied” with 8 indicators and “Completely Satisfied” with 2 indicators of Life Satisfaction Dimension, and produced a Life Satisfaction Index of 7.40 (Happy). Farmers said that they were “Satisfied” with the 3 indicators of Affection Dimension and produced the Affection Index of 6.64 (Happy). Farmers said that they were “satisfied” with 6 indicators of Eudaimonia Dimension and produced the Eudaimonia Index of 7.74 (Happy). It can be concluded that the Happiness Index of smallholder layer chicken farmers in rural areas of East Java Province was 7.28 and classified as “Happy”.